Copper-doped cotton-like malleable electrospun bioactive glass fibers for wound healing applications - Liverani, Liliana; Reiter, Theresa; Zheng, Kai; Neščáková, Zuzana; Boccaccini, Aldo R. (Materials Letters: X, 2022)
The combination of electrospinning and sol-gel methods is attracting the interest of the scientific community for developing three-dimensional bioactive glass (BG)-based fibers. This paper reports the fabrication of cotton-like copper-doped BG fibers by combining electrospinning and sol-gel techniques. Acellular bioactivity in simulated body fluid, ion release, cell viability and scratch cell tests were performed. Results showed that copper was successfully incorporated in the fibers and Cu ions were released in limited concentration over seven days. The presence of copper delayed the mineralization of the fibers upon immersion in simulated body fluid (SBF), but it did not affect keratinocyte viability and migration. Wound closure in the scratch cell test was achieved in 48 h for all the investigated samples.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Bioactive glass; Copper; Electrospinning; Sol-gel; Wound healing